The impact of adhering to sustainable harvesting guidelines on the total photosynthetic capacity of Taxus Canadensis - Sarah Martin; Manuel Lamontagne (The Forestry Chronicle)
Foliage of Canada yew (Taxus canadensis Marsh.) is commercially harvested for extracting taxanes used in anticancer pharmaceutical products. According to New Brunswick harvesting guidelines, only the last three years growth from four out of every five branches should be harvested. A study conducted in the understory of mixedwoods and tolerant hardwoods in northwestern New Brunswick estimated the impact of harvesting foliage on net photosynthetic activity of the residual plant. Net photosynthesis was measured on foliage of current to five-years-old in June, July and August to determine the contribution of each foliage age class to the photosynthetic capacity of a 6-year-old branch segment. Total biomass of each internode age class (0 to 5 and ≥ 6-years-old) was measured to calculate the impact of tip harvesting on percentage of biomass removed and on photosynthetic capacity. When following New Brunswick harvesting guidelines, harvesting removed 15 to 17% of the last three years growth foliage which corresponds to 24 to 36% of total net photosynthetic capacity. The impact of harvesting is greater on photosynthetic activity than on biomass because it is the young and most photosynthetically active foliage that is harvested.